Characterization of Incidence Rates of Breast Cancer in Public Health Service, Period 2006-2015 [Caracterización de la Incidencia del Cáncer de Mama en Un Servicio Público de Salud Chileno en el Período 2006-2015] - Labbe-Atenas, T (Sociedad Chilena de Obstetricia y Ginecologia, 2022)
Objective: Breast cancer is the leading cause of cancer death in Chilean women. Incidence rates have only been estimated based on population records (2003-2007). Our objective was to estimate the incidence rates in a 10-year period in a health service and portray in words this cohort. Method: Incidence rates were calculated between 2006-2015 by direct method and trends were analyzed with the Prais-Winsten model. The population was defined according to age and stage at diagnosis. Results: Of a total of 2862 cases, the average incidence rate was 66.6 out of 100,000 women. Between 2006-2015, the trend rose in breast cancer diagnosis of 0.63/100,000 annually (p = 0.5; 95% confidence interval: -1.73, 2.99). The highest crude rate of incidence was in the group aged 70 and over (154.8/100,000). 49% correspond to cases diagnosed between 50 and 69 years. 56% were in early stages, stage I, being the most frequent (15.8/100,000). Conclusions: On this research the in cidence rates were higher than the ones reported on previous national reports. Diagnosis is mostly in early stages which differs from other countries in the region, our data can help improve public health policies. © 2022 Sociedad Chilena de Obstetricia y Ginecología.